Legal Analysis of the Regional Regulation of Ngawi Regency on the Management of Passive Telecommunications Infrastructure - Lulus Udjiwati; Wahyuni Aslamiyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid expansion of digital transformation has increased the demand for adaptive and legally coherent governance of passive telecommunications infrastructure, requiring regional governments to formulate regulations that are consistent with the evolving national legal framework. This study aims to analyze the authority of the Ngawi Regency Government in regulating passive telecommunications infrastructure, assess the harmonization of the Draft Regional Regulation with Indonesia's national legislation, and formulate a normative reconstruction model that strengthens legal certainty and adaptive digital governance. This research employs a non-empirical juridical (doctrinal) method using statutory, conceptual, and comparative approaches. Primary legal materials comprise statutes, government regulations, regional regulations, and the Draft Regional Regulation, complemented by secondary and tertiary legal materials, which are analyzed through grammatical, systematic, historical, and teleological interpretation. The findings demonstrate that the regional government's regulatory authority is constitutionally and statutorily justified, although several provisions require further harmonization with the risk-based business licensing regime, spatial planning regulations, and the distribution of governmental authority. The study proposes a regulatory reconstruction model emphasizing legislative harmonization, institutional coordination, digital governance transformation, and infrastructure-sharing mechanisms to enhance legal certainty, administrative effectiveness, and sustainable digital infrastructure governance while contributing to the development of adaptive regional regulatory theory.